Notes to Contribute to the Teaching of Marxism in Contemporary Cuban Society - Lian Roque Roque; Julio Fragoso Fragoso (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
This paper is aimed at teachers of the Philosophy and Society course, tutors, personnel in charge of the educational work and those involved in the task of leading new generations towards a better society by conducting an appropriate ideological and political work. It is inspired by the objectives of the First National Conference of the Party in its attempt to adjust the teaching of Marxism to the present time; thus our purpose is to contribute to the teaching of this theory, considering the political and ideological impact it will have on Cuban youth dealing with the challenges posed by reality.